The relationship between 3D technologies and circular manufacturing using the 10R toolbox - Sarka, Ferenc; Dömötör, Csaba (Design of Machines and Structures, 2025)
In this article, we are looking for a possible connection between the 10R toolkit, which represents the basic concept of the Circular Economy, and 3D technologies (scanning, printing, additive manufacturing, CAxx systems). We will examine each of the 10R tools one-by-one and with the help of examples, suggestions and our own experiments, we will point out opportunities that may even predict a general trend in the future. We criticise the participants in society (population, industry, government). Pointing out that any positive change is only possible with the joint action and change of attitude of the participants.